2014
DOI: 10.4269/ajtmh.13-0509
|View full text |Cite
|
Sign up to set email alerts
|

Association between Moderate-to-Severe Diarrhea in Young Children in the Global Enteric Multicenter Study (GEMS) and Types of Handwashing Materials Used by Caretakers in Mirzapur, Bangladesh

Abstract: Handwashing practices among caretakers of case and control children < 5 years of age enrolled in the Global Enteric Multicenter Study in Mirzapur, Bangladesh were characterized and analyzed for association with moderate-to-severe diarrhea. Soap or detergent ownership was common, yet 48% of case and 47.7% of control caretakers also kept ashes for handwashing, including 36.8% of the wealthiest households. Soap, detergent, and ash were used for multiple hygiene purposes and were kept together at handwashing areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
6
16
0
Order By: Relevance
“…15 The majority of informants reported that soap was kept inside their homes, similar to the 2011 national survey findings, where few (17%) rural Bangladeshi households were observed to have soap and water at their handwashing place. 21 Informants prioritized and limited soap use; bathing was accorded a high priority.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…15 The majority of informants reported that soap was kept inside their homes, similar to the 2011 national survey findings, where few (17%) rural Bangladeshi households were observed to have soap and water at their handwashing place. 21 Informants prioritized and limited soap use; bathing was accorded a high priority.…”
Section: Discussionsupporting
confidence: 51%
“…Although some informants described the removal of germs to prevent diseases as a motivator to wash hands, they believed that germs were present only on visibly dirty hands only. Findings from 23 years ago as well as more recently also suggest that these perceptions among Bangladeshis have not changed, 8,15 highlighting a failure or omission of handwashing with soap promotion during this long period. Perception on the importance of handwashing with soap when hands are visibly dirty is also similar to other research findings from low-income settings.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The presence of soap at a latrine is strongly positively correlated with handwashing after defecation or contact with a child's feces (Luby, Halder, et al 2009, Hoque 2003, Baker et al 2014. However, Bangladeshi households often cite the inconvenience or expense of soap as a barrier to handwashing, and shared latrines make it especially challenging to keep soap near the latrine (ibid.…”
Section: Handwashing Interventionmentioning
confidence: 99%